TANGENTIAL INLET GEOMETRY EFFECTS TO THE RICE HUSK PARTICLES FLOW STRUCTURES IN A RECTANGULAR FURNACE - Windari, Linda
Indonesia is the third largest rice producing country in the world after the People's Republic of China and India. The by-product of processing rice and its waste, namely rice husks, has not been utilized optimally and can cause environmental pollution if not handled properly. Rice husk has a high silica content, so it has the potential to be used for various applications. Silica from rice husks can be obtained by burning rice husks into white ash which is rich in silica content in amorphous form through complete combustion. The complete combustion process occurs when the particle residence time in the furnace is about 21-25 seconds. The technology of burning rice husks is currently not optimal and requires innovation. In this study, a simulation of the dynamics of the flow of air and rice husks in the furnace was carried out using the Ansys Fluent student version 2020 R2 software, the equation used in CFD is the standard k-epsilon equation, the particle density of rice husk is 650 kg/m3. Simulations were carried out on several variations of burner geometry. The simulation results obtained the design of a rice husk burning furnace with 4 tangential air inlets on the burner and 4 secondary air inlets on the bottom of the furnace with an average particle residence time of 22.5 seconds. The maximum particle residence time was obtained at a tangential air inlet angle of 90º, a burner diameter of 30 cm, and a burner length of 90 cm.